Analysis of rural economic restructuring driven by e-commerce based on the space of flows: The case of Xiaying village in central China. (July 2022) - Zhang, Yingnan; Long, Hualou; Ma, Li; Tu, Shuangshuang; Li, Yurui; Ge, Dazhuan
Abstract: In recent years, China's rural areas have undergone intense restructuring motivated by various flows derived from e-commerce, which has triggered a new wave of rural rejuvenation. Attempting to reveal the process and mechanism of rural economic restructuring driven by e-commerce, this paper takes Xiaying village in central China to conduct an empirical study by introducing the theory of "space of flows" and applying the method of semi-structured interview. The results show that e-commerce has become a technical catalyst to the variation of industry structure, employment pattern and household economy. Xiaying village has performed a leap from traditional agriculture to commercial service and constructed a complete e-commerce oriented industry chain, which is distinguished from the traditional path of rural modernization adhering to the gradual evolution of the primary, secondary and tertiary industry in China. In response, the employment pattern is diversified and tends to be de-agriculturalization, thus providing an economic advancement opportunity for rural households. As a matter of fact, rural elites, technology innovation (e-commerce platform), resource endowments and government support all contributed greatly to this restructuring process. What distinguishes it from others is the strong mobility and exchange of urban and rural elements, which functions as the initial engine. Essentially, this transition can be considered as the impact of the network on the geographic space restructuring rural economy. Highlights: China's burgeoning rural e-commerce has triggered a new wave of rural rejuvenation. Fully understanding how the space of flows affects rural economic space. Analyzes the process and mechanism of e-commerce oriented rural economic restructuring from the perspective of elements flows.